The safety of home discharge for low‐risk emergency department patients presenting with coronavirus‐like symptoms during the COVID‐19 pandemic: A retrospective cohort study. Issue 6 (17th August 2020) - Berdahl, Carl T.; Glennon, Nicole C; Henreid, Andrew J; Torbati, Sam S.
Abstract: Objective: There is minimal evidence describing outcomes for emergency department (ED) patients with suspected coronavirus disease 2019 (COVID‐19) infection who are not hospitalized. The study objective was to assess 30‐day outcomes (ED revisit, admission, ICU admission, and death) for low‐risk patients discharged after ED evaluation for COVID‐19. Methods: This was a retrospective cohort study of patients triaged to a COVID‐19 surge area within an urban ED and discharged between March 12 and April 6. Physicians were encouraged to discharge patients if they were well‐appearing with few comorbidities. Data were collected from review of medical records and phone follow‐up, and the analysis was descriptive. Results: Of 452 patients, the median age was 38, and 61.7% had no comorbidities. Chest radiographs were performed for 50.4% of patients and showed infiltrates in 14% of those tested. Polymerase chain reaction testing was performed for 28.3% of patients during the index ED visit and was positive in 35.9% of those tested. Follow‐up was achieved for 75.4% of patients. ED revisits occurred for 13.7% of patients. The inpatient admission rate at 30 days was 4.6%, with 0.7% requiring intensive care. Median number of days between index ED evaluation and return for admission was 5 (interquartile range 3–7, range 1–17). There were no known deaths. Conclusions: A minority of low‐risk patients with suspected COVID‐19 will require hospitalization after being discharged home from the ED. Outpatient management is likely safe for well‐appearing patients with normal vital signs, but patients should be instructed to return for worsening symptoms including labored breathing. Future work is warranted to develop and validate ED disposition guidelines.